Dynamic Aging: Channeled Through Microenvironment - Tan, Qing; Liang, Na; Zhang, Xiaoqian; Li, Jun (Frontiers in Physiology, 2021)
Aging process is a complicated process that involves deteriorated performance at multiple levels from cellular dysfunction to organ degeneration. For many years research has been focused on how aging changes things within cell. However, new findings suggest that microenvironment, circulating factors or intercellular communications could also play important roles in the dynamic progression of aging. These out-of-cell mechanisms pass on the signals from the damaged aging cells to other healthy cells or tissues to promote systematic aging phenotypes. This review discusses the mechanisms of how senescence, NAD metabolism, inflammaging and circulating factors change microenvironment to regulate systematic aging, as well as the potential therapeutic strategies based on these findings for anti-aging interventions.